1993
DOI: 10.1148/radiology.186.2.8421758
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial percutaneous biopsy technique with automated biopsy devices: value in improving accuracy and negative predictive value.

Abstract: Three hundred percutaneous biopsies were performed in 267 consecutive patients by means of a coaxial technique with use of 18- and 20-gauge automated cutting biopsy devices and 22-gauge aspiration needles. Thoracic, hepatic, renal, pancreatic, adrenal, splenic, retroperitoneal, and musculoskeletal soft-tissue masses were sampled. For malignant masses (229 cases), the sensitivity was 79% for cytologic analysis, 88% for histologic analysis, and 92% for both combined. In benign disease (71 cases), a correct speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
90
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 0 publications
7
90
1
1
Order By: Relevance
“…Despite the popularity of automated systems for obtaining tissue samples in several solid organs 3 , their use in lung lesions has been very restricted in our country. Previous studies have demonstrated the advantage of the diagnostic yield of the cutting needle biopsy, with acceptable incidence of complications, when compared to fine-needle aspiration biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the popularity of automated systems for obtaining tissue samples in several solid organs 3 , their use in lung lesions has been very restricted in our country. Previous studies have demonstrated the advantage of the diagnostic yield of the cutting needle biopsy, with acceptable incidence of complications, when compared to fine-needle aspiration biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for non-carcinomatous lesions, the accuracy of the method is inferior, reported in the range of 46% to 68% [2][3][4] . Difficulties in diagnosing benign lesions and the unavailability of a cytopathologist in the radiology department have mandated the need to perform biopsies that could supply material for histological analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We reason that this lower number of passes would likely decrease procedure time without compromising the yield or the safety of the procedure based on our results, and, therefore, the use of larger gauge needle is supported. There are multiple studies that have shown core biopsies to be superior to fine-needle aspiration biopsies [2,10,11]. The exact reason for the superior rate of yield with core biopsy has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous CTguided needle lung biopsy has a high diagnostic accuracy and is a well-established procedure for obtaining a cytological evaluation of pulmonary nodules [2,3]. Factors affecting diagnostic accuracy are lesion size, immediate on-site sample evaluation by a cytologist, and technique, including type of biopsy device [4][5][6][7][8][9][10]. A previous study has shown core biopsies to be a more accurate method of tissue sampling without increasing risk of complications when compared to fine-needle aspiration [11].…”
Section: Introductionmentioning
confidence: 99%